Perkawinan di Desa Kabalutan Kabupaten Tojo Una-Una Perspektif Hukum Perkawinan Indonesia - Nurul Miqat; Manga Patila; Bustamin Daeng Kunu; Nurhayati Mardin; Sunardi Purwanda (Universitas Airlangga, 2023)
AbstractMarriage is an inner and outer bond between a man and a woman who becomes husband and wife with the aim of eternal marriage, obtaining happiness and having children. So that the goal of eternal marriage can be realized, then the provisions stipulated in the Marriage Law No. 1 of 1974 must be obeyed, one of which is marriage without coercion and the age limit for marriage, Kabalutan Village with local wisdom which has a tradition, if a man and a woman are found together after 12 o’clock at night, then by community leaders the couple is immediately married, an immature marriage causes easy divorce. Divorce that occurs due to couples who are not physically and mentally ready, so that the divorce rate in Kabalutan Village increases, triggers Kabalutan Village to be known as Kampung Janda. However, in recent years, based on the results of deliberations between community leaders and traditional leaders, the sanctions were later changed to sanctions for lifting stones (baka batu) of at least 2 cubic meters. These sanctions make people afraid of violating them and these sanctions are very effective in reducing the number of widows, especially widows at a young age. This paper uses a juridical-empirical research method, the conclusion of this paper is that the nickname of the widow’s village in Kablutan Village, Central Sulawesi is the impact of a living and developing tradition, namely by sanctioning direct marriage of male and female couples who are found alone at 12 o’clock at night.Keywords: Widow Village; Marriage Law; Divorce. AbstrakPerkawinan adalah ikatan lahir bathin antara seorang laki laki dan perempuan menjadi suami isteri dengan tujuan perkawinan yang kekal, mendapatkan kebahagiaan dan mempunyai keturunan. Nagar tujuan perkawinan kekal dapat terwujud, maka ketentuan yang diatur dalam UU Perkawinan No 1 Tahun 1974 harus ditaati, salah satunya yakni perkawinan tanpa paksaan dan batas usia kawin, Desa Kabalutan dengan kearifan lokal memiliki tradisi, jika seorang laki laki dan seorang perempuan kedapatan berduaan diatas jam 12 malam, maka oleh tokoh masyarakat pasangan tersebut langsung diberikan sanksi yakni dikawinkan, perkawinan yang tidak matang menyebabkan mudahnya perceraian. perceraian yang terjadi akibat pasangan yang tidak siap jiwa raga, sehingga angka perceraian di Desa Kabalutan meningkat, dan menjadi pemicu Desa Kabalutan dikenal dengan julukan Kampung Janda. Akan tetapi beberapa tahun belakangan, berdasarkan hasil musyawarah tokoh masyarakat dan tokoh adat, sanksi kemudian diganti menjadi sanksi mengangkat batu (baka batu) minimal 2 kubik. sanksi tersebut membuat masyarakat takut melanggarnya dan Sanksi tersebut sangat efektif mengurangi angka janda, terutama janda diusia muda. Tulisan ini menggunakan metode penelitian yuridis-empiris, kesimpulan dari tulisan ini , bahwa julukan kampung janda di Desa Kablutan Sulawesi Tengah adalah dampak dari tradisi yang hidup dan berkembang yakni dengan sanksi mengawinkan langsung pasangan laki-laki dan perempuan yang kedapatan berduaan diatas jam 12 malam.Kata Kunci: Kampung Janda; Hukum Perkawinan; Perceraian.